Self‐navigated prospective motion correction for 3D‐EPI acquisition. Issue 1 (28th March 2022) - Bayih, Samuel Getaneh; Jankiewicz, Marcin; Alhamud, A.; van der Kouwe, André J. W.; Meintjes, Ernesta M.
Abstract : Purpose: Although 3D EPI is more susceptible to motion artifacts than 2D EPI, it presents some benefits for functional MRI, including the absence of spin‐history artifacts, greater potential for parallel imaging acceleration, and better functional sensitivity in high‐resolution imaging. Here we present a self‐navigated 3D‐EPI sequence suitable for prospective motion‐corrected functional MRI without additional hardware or pulses. Methods: For each volume acquisition, the first 24 of the 52 partitions being acquired are accumulated to a new feedback block that was added to the image reconstruction pipeline. After zero‐filling the remaining partitions, the feedback block constructs a volumetric self‐navigator ( vSNav ), co‐registers it to the reference vSNav acquired during the first volume acquisition, and sends motion estimates to the sequence. The sequence then updates its FOV and acquires subsequent partitions with the adjusted FOV, until the next update is received. The sequence was validated without and with intentional motion in phantom and in vivo on a 3T Skyra. Results: For phantom scans, the FOV was updated 0.704 s after acquisition of the vSNav partitions, and for in vivo scans after 0.768 s. Both phantom and in vivo data demonstrated stable motion estimates in the absence of motion. For in vivo acquisitions, prospective head‐pose estimates using the vSNav' s and retrospective estimates with FLIRT (FMRIB's Linear Image Registration Tool) agreed to within 0.23 mm (< 10% of the slice thickness) and 0.14° in all directions. Conclusion: Depending when motion occurs during a volume acquisition, the proposed method fully corrects the FOV and recovers image quality within one volume acquisition.